(untitled) (Research, Society and Development, 2022)
Information represents the focus of the digital revolution, and gradually both privacy and intimacy became necessary, in particular citizens’ personal data, with this, the General Data Protection Law - LGPD, was regulated, leading Brazil to the protection level, presented by this new reality. This law brings principles, rights and obligations of data related to people, which brings together a set of control elements, enabling the fulfillment of the foreseen guarantees whose ballast is based on the protection of human rights. It safeguards fundamental principles, such as the right to freedom and privacy, the free development of the person’s personality, stating good faith in the processing of personal data through rules, and controls to secure the information. In this sense, this article presents a brief Introduction, which describes in general terms about Law nº 13.709/2018 (General Data Protection Law) in Brazil. Subsequently, it is explained about the methodological procedures, which for this article was in the form of a narrative literature review, thus providing robustness and foundation for the study. Soon after, a theoretical foundation is presented, with some important points of the LGPD, such as the data regulated by the aforementioned law; its legal principles; its legal bases; its agents and responsibilities. Then there is a discussion on the subject, and finally the conclusion of this article is presented.